Corporate Governance dalam meningkatkan Integritas Laporan Keuangan Entitas Bisnis - Lailah Fujianti; Eka Putri Wahyuningtias (Media Ilmiah Akuntansi, 2021)
This study aims to determine corporate governance (CG) and the specialty of industry auditors on the integrity of financial statements in manufacturing companies listed on the Indonesia Stock Exchange. The sample in this study were 99 in various industrial sectors from 2016 to 2018 manufacturing companies listed on the Indonesia Stock Exchange. The sample selection method is purposive sampling method. The results of this study indicate that the CG variable which includes independent commissioners, institutional ownership, audit committee effect to financial statement integrity, while managerial ownership have no effect on the integrity of financial statements.